(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2024)
This research highlights the synergistic impact of including varying steel fiber contents and size of coarse aggregate on the concrete’s mechanical characteristics, including compression strength, workability, splitting tensile strength, and stress-strain correlations under compression stress. The study investigated steel fiber percentages ranging from 0% to 2% with increments of 0.5% and coarse aggregate maximum sizes, namely (9.5mm, 12.5mm and 19mm). The study entailed the production and examination of a total of fifteen concrete samples, comprising three cubes and two cylinders for each concrete mixture. The results demonstrated that the compressive strength of concrete mixes lacking steel fibers shows a positive relationship with the largest size of coarse aggregate. However, the inclusion of steel fibers causes a reduction in compressive strength as the maximum size of coarse aggregate increases. Finer coarse aggregate sizes resulted in the highest tensile strength. Moreover, the study showed that including hooked-end steel fibers (SF) enhances the stiffness of concrete cylinders and allows for deformation without fracture. And, the influence of maximum coarse aggregate size on stress-strain behavior is negligible. These findings emphasize the significance of taking into account both the overall size and the inclusion of SF in mixes of concrete to improve the compressive and tensile strength, stress-strain responses, and overall performance.